Beneficial health effects of glucosinolates-derived isothiocyanates on cardiovascular and neurodegenerative diseases - Muhammad Kamal, Ramla; Abdull Razis, Ahmad Faizal; Mohd Sukri, Nurul Syafuhah; Perimal, Enoch Kumar; Ahmad, Hafandi; Patrick, Rollin; Djedaini-Pilard, Florence; Mazzon, Emanuela; Rigaud, Sébastien (MDPI, 2022)
Neurodegenerative diseases (NDDs) and cardiovascular diseases (CVDs) are illnesses that affect the nervous system and heart, all of which are vital to the human body. To maintain health of the human body, vegetable diets serve as a preventive approach and particularly Brassica vegetables have been associated with lower risks of chronic diseases, especially NDDs and CVDs. Interestingly, glucosinolates (GLs) and isothiocyanates (ITCs) are phytochemicals that are mostly found in the Cruciferae family and they have been largely documented as antioxidants contributing to both cardio- and neuroprotective effects. The hydrolytic breakdown of GLs into ITCs such as sulforaphane (SFN), phenylethyl ITC (PEITC), moringin (MG), erucin (ER), and allyl ITC (AITC) has been recognized to exert significant effects with regards to cardio- and neuroprotection. From past in vivo and/or in vitro studies, those phytochemicals have displayed the ability to mitigate the adverse effects of reactive oxidation species (ROS), inflammation, and apoptosis, which are the primary causes of CVDs and NDDs. This review focuses on the protective effects of those GL-derived ITCs, featuring their beneficial effects and the mechanisms behind those effects in CVDs and NDDs